2022
DOI: 10.1177/1071181322661177
|View full text |Cite
|
Sign up to set email alerts
|

The TRUSTS Work System Resilience Framework: A Foundation for Resilience-Aware Development and Transition

Abstract: Despite decades of effort to improve information technology (IT) transition, the success rate remains low with each failure representing substantial losses of time, money, and resources. When technologies do transition, they often are ignored and worked around. Worse, they may disrupt work or interfere with work-system responses to challenges. We posit that a systems-centered approach to transition grounded in complex-systems science and resilience engineering can significantly improve technology adoption rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…The RAD-X generated 15 user stories in one hour. Three resilience engineering experts coded each user story using the TRUSTS framework (Neville et al, 2022) to characterize their relevance to work system resilience. Coding showed that 13 of 15 (87%) were resilience-focused, while two (13%) did not support resilience but instead described basic functionality.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The RAD-X generated 15 user stories in one hour. Three resilience engineering experts coded each user story using the TRUSTS framework (Neville et al, 2022) to characterize their relevance to work system resilience. Coding showed that 13 of 15 (87%) were resilience-focused, while two (13%) did not support resilience but instead described basic functionality.…”
Section: Resultsmentioning
confidence: 99%
“…Recent research has argued that a failure to consider work system resilience during development can result in failed technology transition (Neville et al, 2022). One response was to introduce the paradigm of Resilience Aware Development (RAD): The idea that a technology's effects on work system resilience must be considered throughout its development, especially in cases of high-consequence work.…”
Section: Overviewmentioning
confidence: 99%
“…This value extends beyond developing ethical AI. NDM approaches have been used to glean insights on developing trustworthy AI (e.g., Dorton and Harper, 2022 and Dorton, 2022 ) and resilient AI technologies (e.g., Neville et al, 2022 ). In summary, we have attempted to craft our argument while providing different messages to two different audiences.…”
Section: Discussionmentioning
confidence: 99%
“…We have developed a framework that specifies the characteristics of work systems that enable resilience (Neville et al, 2022). This framework, called the Transform with Resilience during Upgrades to Socio-Technical Systems, or TRUSTS, is the basis of an effort to improve system development methodology and, by reducing negative impacts on work system resilience, improve the likelihood of successful technology transition and use.…”
Section: Technology Development That Preserves Work-system Resilience...mentioning
confidence: 99%